The fire regime response of a reintroduced endangered species. Issue 7 (10th December 2021) - Lindenmayer, David; MacGregor, Christopher; Blanchard, Wade; Foster, Claire
Abstract : Reintroduction and translocation are widely employed actions in restoration ecology. The broad aim of these activities is to re‐establish populations in places where they formerly existed. However, the success of re‐establishment efforts in terms of responses to key ecosystem processes such as natural disturbances like fires has rarely been quantified. Using the iconic and endangered Australian Eastern Bristlebird ( Dasyornis brachypterus ) as a case study, we quantified associations with fire regime variables in an intact population (surveyed for 17 years) and a translocated population (surveyed for 10 years). Both populations occurred in a similar environment and were surveyed on an (almost) annual basis using the same field protocols. We found that both the intact population and the translocated population of the Eastern Bristlebird were associated with the same key fire regime variable, time since fire, in a broadly similar way. In addition, the probability of species persistence was found to lowest on recently burnt sites. We tentatively suggest that the translocation program has not only successfully re‐established a population of the Eastern Bristlebird but associations with (and resilience to) fire as a key ecological process are similar in both populations. On the basis of our findings, we recommend that in areas where the Eastern Bristlebird occurs prescribed fire management should focus on ensuring there are patches of unburnt vegetation within the fire footprint. This is especially important given the widespread wildfires that have recently occurred throughout south‐eastern Australia.